Composite coating for deicing through electro-thermal photo-thermal conversion and preparation method of composite coating
By using electrothermal photothermal conversion composite coatings prepared with epoxy resin, curing agent, titanium carbide nanoparticles and other materials, the problem that the performance of the existing photothermal deicing coating depends on micro-nano structure and materials is not environmentally friendly, and an efficient, low-cost and environmentally friendly deicing effect is achieved.
Patent Information
- Application Number
- CN202411700248.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The performance of existing photothermal deicing coatings is highly dependent on micro-nano structure design, which is expensive to prepare, difficult to meet the needs of large-scale production, and is susceptible to mechanical damage. The commonly used materials are not environmentally friendly, which limits its wide application.
The electric and thermal light-thermal conversion composite coating is prepared through spraying technology to achieve efficient deicing effect of electric and photothermal heat.
The coating can increase the temperature to above 100°C in 90 seconds at an electrical power density of 0.4W/cm2, and the temperature can increase to above 130°C under irradiation of one sunlight. The melting time of frozen droplets is shortened to 52 seconds, which significantly improves the deicing efficiency and reduces costs.
Smart Images

Figure CN119529637A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to coatings and methods for making the same, and in particular to a composite coating for deicing by electrothermal and photothermal conversion and a method for making the same. Background Art
[0002] Icing is a widespread phenomenon in nature, and often appears on the surfaces of important infrastructure such as aircraft, wind turbines, and high-voltage lines, which has an adverse effect on various industrial processes and may even lead to serious safety hazards. Therefore, how to quickly remove ice from solid surfaces has become a scientific and technological problem that needs to be solved urgently. Traditional mechanical and chemical deicing methods have problems such as low efficiency, environmental pollution, and equipment loss, which limit their effectiveness in practical applications.
[0003] In recent years, solar energy, as a clean energy source, has attracted much attention in anti-icing technology. Photothermal surfaces absorb sunlight and convert it into heat energy, raising the temperature of the solid surface, thereby achieving anti-icing and de-icing effects. Although existing photothermal de-icing coatings have made some progress, they still face many problems and challenges because their performance is highly dependent on the micro-nanostructure design of the surface.
[0004] First, the preparation of micro-nano structures usually requires high-precision processing methods (such as laser processing and electron beam etching), which are not only costly and time-consuming, but also difficult to meet the needs of large-scale production. Secondly, micro-nano structures are easily degraded due to mechanical damage (such as wear and scratches) in practical applications, resulting in a significant decrease in photothermal efficiency. In addition, many existing surface modification technologies rely on environmentally unfriendly materials such as organic solvents and fluorine chemicals, further limiting their widespread application.
[0005] Therefore, it is urgent to develop a new type of anti-icing and de-icing coating that does not rely on micro-nano structures and has all-weather adaptability and high efficiency, which has become an urgent need in practical applications. The design of such coatings not only needs to overcome the limitations of existing technologies, but also needs to take into account low cost, sustainability and environmental friendliness to better meet the needs of industrial and social development. Summary of the invention
[0006] Purpose of the invention: In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide an all-weather anti-icing electrothermal-photothermal conversion deicing composite coating. Another purpose of the present invention is to provide a convenient and practical method for preparing the electrothermal-photothermal conversion deicing composite coating.
[0007] Technical solution: The composite coating for electrothermal and photothermal conversion deicing described in the present invention includes the following raw materials in parts by weight: 3.5 to 6 parts of epoxy resin, 3.5 to 6 parts of curing agent, 1 to 2 parts of titanium carbide, and 18 to 20 parts of anhydrous ethanol.
[0008] Furthermore, the curing agent is E51 curing agent with a viscosity of 2000-3000 mPa·S, and the epoxy resin is E51 bisphenol A epoxy resin with a viscosity of 11000-14000 mPa·S.
[0009] Furthermore, the average particle size of titanium carbide is 50 nm.
[0010] The method for preparing a composite coating for electrothermal and photothermal conversion deicing according to the present invention comprises the following steps:
[0011] Step 1, using anhydrous ethanol as a solvent, adding epoxy resin and curing agent and stirring at room temperature until dissolved to obtain a homogeneous solution A;
[0012] Step 2, applying the homogeneous solution A obtained in step 2 on the surface of a clean substrate by scraping, and vacuum drying to form an insulating layer on the clean substrate;
[0013] Step 3, laying a conductive copper foil on the insulating layer obtained in step 2;
[0014] Step 4: using anhydrous ethanol as solvent, adding titanium carbide nanoparticles and magnetically stirring them evenly, then adding epoxy resin and curing agent, magnetically stirring until dissolved, and then ultrasonically dispersing them to form a homogeneous solution B;
[0015] Step 5, spraying the homogeneous solution B obtained in step 4 on the surface of the product obtained in step 3, and vacuum drying to obtain a composite coating.
[0016] Furthermore, in step 1, the mass ratio of anhydrous ethanol, epoxy resin and curing agent is 2-3:0.5-2:0.5-2.
[0017] Furthermore, in step 2, the vacuum drying temperature is 60-80°C and the time is 2-4 hours. The substrate is an iron plate, and the surface of the iron plate is first treated with 800-2000 mesh sandpaper to remove surface impurities, and then ultrasonically cleaned for 10-20 minutes to form a clean surface.
[0018] Furthermore, in step 4, the ratio of anhydrous ethanol, titanium carbide, epoxy resin: curing agent is 7.5-8.5: 1-2: 0.25-1: 0.25-1. The speed of magnetic stirring is 500-600 rpm, and the time is 40-60 min.
[0019] Furthermore, in step five, the spraying is air spraying. Air spraying can usually cover smaller areas better than traditional brushing or roller coating, and form a uniform thin layer on the surface of complex shapes. Due to the presence of airflow, the spray atomized particles are smaller, and the spraying quality is good and smooth. The air spraying operation requires a high level of technical proficiency, and it is necessary to master the appropriate spraying distance, spray gun angle, hand speed, etc. A slight deviation may cause problems such as uneven coating, sagging, and overspray. The compressed air pressure for spraying is 0.4-0.8MPa. The distance between the substrate and the spray gun nozzle during the spraying process is 15-20cm, the spraying time is 30-60s, and the vacuum drying temperature is 60-80℃ for 4-8 hours.
[0020] Preparation principle: The insulating layer is prepared by optimizing the ratio of epoxy resin and anhydrous ethanol. The insulating layer serves to isolate the substrate from the electrothermal coating, preventing safety accidents caused by current leakage, while reducing heat loss and ensuring the deicing effect of the coating. The epoxy resin coating also forms a strong bond with the substrate, improving the stability and durability of the coating. The key to the present invention lies in the preparation of the conductive coating. The conductive particles need to be evenly distributed inside the conductive coating to form a dense conductive network to achieve stable electrothermal conversion. To this end, the best conductivity and thermal conversion effect are obtained by adjusting the ratio of epoxy resin to titanium carbide (TiC) nanoparticles. The coating can be applied to various solid surfaces through spraying technology and exhibits excellent electrothermal and photothermal conversion performance. Based on the excellent photothermal conversion ability and good conductivity of titanium carbide nanoparticles, the coating can simultaneously achieve efficient deicing effects of electrothermal and photothermal.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant features:
[0022] 1. Using epoxy resin with excellent corrosion resistance, high temperature resistance and insulation performance as a binder, combined with the electrothermal effect and photothermal effect of titanium carbide nanoparticles, a photoelectric thermal composite coating with long-term stability is prepared;
[0023] 2. The electrothermal and photothermal composite coating of the present invention has excellent performance in electrothermal and photothermal conversion. 2 At an electric power density of 100 W / cm2, the coating can raise the temperature to over 100°C within 90 seconds. 2 ) , the coating temperature can rise to above 130°C within 300 seconds; in addition, when 0.2W / cm 2 The power density of 1 sun (1sun, 0.1W / cm 2 ), the melting time of the frozen droplets can be shortened to 52 seconds, which is 4.5 times shorter than that of the smooth substrate. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a schematic diagram of a composite coating prepared by the present invention;
[0025] Figure 2 The present invention is a 1 sun light (1sun, 0.1W / cm 2 ) under the irradiation of temperature rise diagram;
[0026] Figure 3 The present invention is 0.4W / cm 2 Temperature rise diagram under electric power density;
[0027] Figure 4 is a temperature rise diagram of Example 2 of the present invention under different lighting conditions;
[0028] Figure 5 is a temperature rise diagram of Example 2 of the present invention at different electric power densities;
[0029] Figure 6 is a diagram showing the delayed freezing effect of Example 2 of the present invention under different conditions;
[0030] Figure 7 2 is a diagram showing the deicing effect of Example 2 of the present invention under different conditions. DETAILED DESCRIPTION
[0031] Unless otherwise specified, the materials, reagents, instruments, etc. used in the following examples can be obtained from commercial sources. Experimental methods without specific conditions in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0032] Example 1
[0033] A method for preparing a composite coating for electrothermal and photothermal conversion deicing, comprising the following steps:
[0034] S1. Treat the surface of the iron plate with 800-grit sandpaper and put it into an ultrasonic cleaner to clean the surface for 20 minutes to form a clean surface.
[0035] S2. Add 3 g of E51 bisphenol A epoxy resin and 3 g of E51 curing agent into 12 g of anhydrous ethanol and stir for 20 minutes to form a homogeneous solution A.
[0036] S3. Apply the homogeneous solution A onto the clean iron plate substrate 1 by blade coating, and dry at 60° C. for 2 hours to form an insulating layer 2.
[0037] S4, cut two 3 cm*0.5 cm conductive copper foils 3 and lay them on both sides of the insulating layer 2.
[0038] S5. Add 1 g of titanium carbide nanoparticles to 8 g of anhydrous ethanol, stir magnetically at 600 rpm for 20 minutes, add 0.5 g of E51 bisphenol A epoxy resin and 0.5 g of E51 curing agent to the solution, continue magnetic stirring for 40 minutes, and then perform ultrasonic dispersion for 10 minutes to form a homogeneous solution B.
[0039] S6. Add the homogeneous solution B into the spray gun, spray with compressed air pressure of 0.4 MPa, keep the distance between the substrate and the spray gun nozzle of 15 cm during the spraying process, and spray for 30 seconds; after spraying, dry at 60°C for 4 hours to obtain the photoelectric thermal coating 4.
[0040] The electrothermal photothermal conversion deicing composite coating obtained in this embodiment was subjected to an electrothermal photothermal heating test performance test, and the experimental conditions were a temperature of 25±2°C and a humidity of 60±5%. The results showed that: under 1 sun (1sun, 0.1W / cm 2 ) irradiated by 0.4W / cm 2 Under the electric power density, its electrothermal conversion temperature can reach about 85℃ in 90s.
[0041] Example 2
[0042] A method for preparing a composite coating for electrothermal and photothermal conversion deicing, comprising the following steps:
[0043] S1. Treat the surface of the iron plate with 800-grit sandpaper and put it into an ultrasonic cleaner to clean the surface for 10 minutes to form a clean surface.
[0044] S2. Add 3 g of E51 bisphenol A epoxy resin and 3 g of E51 curing agent into 12 g of anhydrous ethanol and stir for 20 minutes to form a homogeneous solution A.
[0045] S3. Apply the homogeneous solution A onto the clean iron plate substrate 1 by blade coating, and dry at 60° C. for 2 hours to form an insulating layer 2.
[0046] S4, cut two 3 cm*0.5 cm conductive copper foils 3 and lay them on both sides of the insulating layer 2.
[0047] S5. Add 1.5 g of titanium carbide nanoparticles to 7.5 g of anhydrous ethanol, stir magnetically at 600 rpm for 20 minutes, add 0.5 g of E51 bisphenol A epoxy resin and 0.5 g of E51 curing agent to the solution, continue magnetic stirring for 40 minutes, and then perform ultrasonic dispersion for 10 minutes to form a homogeneous solution B.
[0048] S6. Add the homogeneous solution B into the spray gun, spray with compressed air pressure of 0.6 MPa, keep the distance between the substrate and the spray gun nozzle of 15 cm during the spraying process, and spray for 30 seconds; after spraying, dry at 60°C for 4 hours to obtain the photoelectric thermal coating 4.
[0049] The electrothermal photothermal conversion deicing composite coating obtained in this embodiment was subjected to an electrothermal photothermal heating test performance test, and the experimental conditions were a temperature of 25±2°C and a humidity of 60±5%RH. The results showed that: under 1 sun (1sun, 0.1W / cm 2 ) irradiated by 0.4W / cm 2 At an electric power density of 0.2W / cm 2 The power density of 1 sun (1sun, 0.1W / cm 2 ), the melting time of the frozen droplets was shortened to 52s.
[0050] Example 3
[0051] A method for preparing a composite coating for electrothermal and photothermal conversion deicing, comprising the following steps:
[0052] S1. Treat the surface of the iron plate with 800-grit sandpaper and put it into an ultrasonic cleaner to clean the surface for 20 minutes to form a clean surface.
[0053] S2. Add 3 g of E51 bisphenol A epoxy resin and 3 g of E51 curing agent into 12 g of anhydrous ethanol and stir for 20 minutes to form a homogeneous solution A.
[0054] S3. Apply the homogeneous solution A onto the clean iron plate substrate 1 by blade coating, and dry at 60° C. for 2 hours to form an insulating layer 2.
[0055] S4, cut two 3 cm*0.5 cm conductive copper foils 3 and lay them on both sides of the insulating layer 2.
[0056] S5. Add 2 g of titanium carbide nanoparticles to 7 g of anhydrous ethanol, stir magnetically at 600 rpm for 20 minutes, add 0.5 g of E51 bisphenol A epoxy resin and 0.5 g of E51 curing agent to the solution, continue magnetic stirring for 40 minutes, and then perform ultrasonic dispersion for 10 minutes to form a homogeneous solution B.
[0057] S6. Add the homogeneous solution B into the spray gun, spray with compressed air pressure of 0.4 MPa, keep the distance between the substrate and the spray gun nozzle of 20 cm during the spraying process, and spray for 40 seconds; after spraying, dry at 60°C for 4 hours to obtain the photoelectric thermal coating 4.
[0058] The electrothermal photothermal conversion deicing composite coating obtained in this embodiment was subjected to an electrothermal photothermal heating test performance test, and the experimental conditions were a temperature of 25±2°C and a humidity of 60±5%. The results showed that: under 1 sun (1sun, 0.1W / cm 2 ) irradiated by 0.4W / cm 2 At an electric power density of 1.5 W, the electrothermal conversion temperature can reach 105°C in 90 seconds.
[0059] Example 4
[0060] A method for preparing a composite coating for electrothermal and photothermal conversion deicing, comprising the following steps:
[0061] S1. Treat the surface of the iron plate with 2000-grit sandpaper and put it into an ultrasonic cleaner to clean the surface for 15 minutes to form a clean surface.
[0062] S2. Add 2.5 g of E51 bisphenol A epoxy resin and 2.5 g of E51 curing agent into 12 g of anhydrous ethanol and stir for 20 minutes to form a homogeneous solution A.
[0063] S3. Apply the homogenized solution A onto the clean iron plate substrate 1 by a doctor blade coating method. Dry at 80° C. for 4 hours to form an insulating layer 2.
[0064] S4, cut two 3 cm*0.5 cm conductive copper foils 3 and lay them on both sides of the insulating layer 2.
[0065] S5. Add 1 g of titanium carbide nanoparticles to 6 g of anhydrous ethanol, stir magnetically at 500 rpm for 20 minutes, add 1 g of E51 bisphenol A epoxy resin and 1 g of E51 curing agent to the solution, continue magnetic stirring for 20 minutes, and then perform ultrasonic dispersion for 10 minutes to form a homogeneous solution B.
[0066] S6. Add the homogeneous solution B into the spray gun, spray with compressed air pressure of 0.8 MPa, keep the distance between the substrate and the spray gun nozzle of 18 cm during the spraying process, and spray for 60 s; after spraying, dry at 80°C for 8 hours to obtain the photoelectric thermal coating 4.
[0067] The electrothermal photothermal conversion deicing composite coating obtained in this embodiment was subjected to an electrothermal photothermal heating test performance test, and the experimental conditions were a temperature of 25±2°C and a humidity of 60±5%. The results showed that: under 1 sun (1sun, 0.1W / cm 2 ) irradiated, its photothermal conversion temperature can reach 125°C in 600s, and at 0.4W / cm 2Under the electric power density, the electrothermal conversion temperature can reach about 60℃ in 90s.
[0068] Example 5
[0069] A method for preparing a composite coating for electrothermal and photothermal conversion deicing, comprising the following steps:
[0070] S1. Treat the surface of the iron plate with 1200-grit sandpaper and put it into an ultrasonic cleaner to clean the surface for 15 minutes to form a clean surface.
[0071] S2. Add 4.5 g of E51 bisphenol A epoxy resin and 4.5 g of E51 curing agent into 12 g of anhydrous ethanol and stir for 20 minutes to form a homogeneous solution A.
[0072] S3. Apply the homogeneous solution A onto the clean iron plate substrate 1 by blade coating, and dry at 70° C. for 3 hours to form an insulating layer 2.
[0073] S4, cut two 3 cm*0.5 cm conductive copper foils 3 and lay them on both sides of the insulating layer 2.
[0074] S5. Add 1 g of titanium carbide nanoparticles to 6 g of anhydrous ethanol, stir magnetically at 550 rpm for 20 minutes, add 1.5 g of E51 bisphenol A epoxy resin and 1.5 g of E51 curing agent to the solution, continue magnetic stirring for 30 minutes, and then perform ultrasonic dispersion for 10 minutes to form a homogeneous solution B.
[0075] S6. Add the homogeneous solution B into the spray gun, spray with compressed air pressure of 0.7 MPa, keep the distance between the substrate and the spray gun nozzle at 17 cm during the spraying process, and spray for 50 s; after spraying, dry at 70° C. for 6 hours to obtain the photoelectric thermal coating 4.
[0076] The electrothermal photothermal conversion deicing composite coating obtained in this embodiment was subjected to an electrothermal photothermal heating test performance test, and the experimental conditions were a temperature of 25±2°C and a humidity of 60±5%. The results showed that: under 1 sun (1sun, 0.1W / cm 2 ) irradiated by 0.4W / cm 2 At an electric power density of 1.5 kW, the electrothermal conversion temperature can reach 43°C in 90 seconds.
[0077] like Figure 2 Examples 1 to 5 show the coatings with different TiC contents under 1 sun (1sun, 0.1W / cm 2) under irradiation, the results show that with the increase of TiC content, the photothermal conversion performance of the composite coating is gradually enhanced. Examples 4 and 5 are mainly based on Example 1, in which the content of epoxy resin and curing agent is increased, and the photothermal temperature rise of the coating is slightly reduced.
[0078] like Figure 3 Examples 1 to 5 show that coatings with different TiC contents have a 2 The temperature change curve under the electric power density shows that with the increase of TiC content, the electrothermal conversion performance of the composite coating gradually increases, and the temperature rises accordingly. Examples 4 and 5 mainly change the content of epoxy resin and curing agent on the basis of Example 1, and the electrothermal temperature rise of the coating decreases rapidly. Therefore, we can conclude that the increase of epoxy resin will affect the conductivity of the coating, and then affect the electrothermal temperature rise of the coating.
[0079] In the above embodiments, the heating results of Embodiment 2 and Embodiment 3 are similar, but Embodiment 2 uses less TiC nanoparticles, saving costs, so Embodiment 2 is a preferred embodiment.
[0080] like Figure 4 As shown in the figure, the photothermal heating effect diagram of Example 2 is shown. 2 ) irradiated, the coating temperature rose to 132°C within 600s and remained stably at 132°C; 0.7 sun (0.7sun, 0.07W / cm 2 ) irradiation, the coating temperature rises to 115°C within 600s and remains stably at 115°C; 0.5 sun (0.5sun, 0.05W / cm 2 ) irradiated, the coating temperature rose to 91°C within 600s and remained stable at 91°C; 0.3 sun (0.3sun, 0.03W / cm 2 ) irradiation, the coating temperature rises to 65℃ within 600s and remains stably at 65℃.
[0081] like Figure 5 As shown in the figure, the electric heating effect diagram of Example 2 is shown. 2 At an electric power density of 0.2 W / cm 2 At an electric power density of 0.1 W / cm 2 At an electric power density of 0.05 W / cm 2 Under the electric power density of , the coating temperature rises to 45℃ within 600s and remains stably at 45℃.
[0082] like Figure 6 , a delayed freezing test was conducted on Example 2. In the absence of sunlight and power, the time required for the water droplets to completely freeze was 214 seconds; at 0.05W / cm 2 At an electric power density of 0.5 sun (0.5sun, 0.05W / cm 2 ) , the freezing time was further extended to 2165 seconds, which is 9.1 times longer than that under no light conditions. 2 ) and 0.05W / cm 2 Under the conditions of combined photoelectric and thermal conditions with high electrical power density, a delayed freezing test was conducted on Example 2, and the results showed that the droplets were completely evaporated within 170 minutes.
[0083] like Figure 7 , deicing test was conducted on Example 2. First, the melting test of frozen droplets was conducted without any external heat source. The results showed that the droplets were completely melted in 233 seconds. Then, under 1 sun (1sun, 0.1W / cm 2 ) irradiated, the melting time of the droplets was significantly shortened to 134 seconds, demonstrating the good effect of photothermal conversion in accelerating ice melting. 2 When tested under the condition of electric power density of 100W / cm2, the droplet melting time was 184 seconds, which was 1.3 times shorter than that under the condition of no heat source, further confirming the effectiveness of electrothermal conversion in the deicing process. Finally, the deicing effect of Example 2 was tested by combining photothermal and electrothermal. 2 ) and 0.05W / cm 2 Under the conditions of combined photoelectric and thermal power density, the melting time of frozen droplets on the coating was shortened to 69s. Compared with a single heat source, the effect was improved several times, which also verified the necessity of combining photothermal and electrothermal deicing and had a synergistic effect.
[0084] Table 1 shows the melting time of Example 2 under various conditions
[0085] Light intensity Electric power density Melting time 0sun <![CDATA[0.05W / cm 2 ]]> 204s 0.5sun <![CDATA[0W / cm 2 ]]> 201s 0.5sun <![CDATA[0.05W / cm 2 ]]> 173s 0.7sun <![CDATA[0W / cm 2 ]]> 172s 0.5sun <![CDATA[0.1W / cm 2 ]]> 152s 0sun <![CDATA[0.2W / cm 2 ]]> 143s 0.7sun <![CDATA[0.05W / cm 2 ]]> 133s 0.5sun <![CDATA[0.2W / cm 2 ]]> 125s 0.7sun <![CDATA[0.1W / cm 2 ]]> 113s 1sun <![CDATA[0.05W / cm 2 ]]> 102s 0.7sun <![CDATA[0.2W / cm 2 ]]> 67s 1sun <![CDATA[0.2W / cm 2 ]]> 52s
[0086] Example 6
[0087] This example aims to explore the effect of the ratio of epoxy resin and anhydrous ethanol used in preparing the insulating layer 2 on the performance of the insulating layer 2 .
[0088] The remaining steps of this comparative example are the same as those of Example 2, with the only difference being that the raw materials in S2 are replaced by: (1) 1g epoxy resin, 1g curing agent, 12g anhydrous ethanol; (2) 2g epoxy resin, 2g curing agent, 12g anhydrous ethanol; (3) 4g epoxy resin, 4g curing agent, 12g anhydrous ethanol. An electric heating test was conducted, and it was found that when the schemes (1) and (2) were adopted, when the content of epoxy resin was reduced to 1g and 2g, the prepared insulating layer 2 could not achieve the insulation effect. When a DC power supply was connected, the current would be transferred to the iron plate of the substrate 1, causing a short circuit, and the coating would not perform electrothermal conversion. Then, when we increased the content of epoxy resin to 2.5g, we found that the coating had restored its conductivity. We implemented scheme (3) and found that when the content of epoxy resin in the insulating layer 2 increased, the thickness of the insulating layer 2 would increase significantly, but it would not affect the photothermal and electrothermal properties of the coating.
[0089] Comparative Example 1
[0090] The remaining steps of this comparative example are the same as those of Example 2, except that the titanium carbide nanometer-sized material is replaced with titanium carbide micrometer-sized material. Photoelectric thermal heating test was performed and the results showed that the micrometer-sized material 2 ) under irradiation, the maximum temperature rise is 109℃, which is 21℃ lower than that of nanomaterials.
[0091] Comparative Example 2
[0092] The remaining steps of this comparative example are the same as those of Example 2, except that the titanium carbide in S5 is replaced with 0.5 g in sequence. The electrothermal photothermal heating performance test was carried out under the experimental conditions of 25±2°C and 60±5% humidity. The results showed that the maximum photothermal heating of the coating was only 85°C, indicating that the heating of the coating was positively correlated with the content of titanium carbide. The higher the content, the higher the maximum heating and the faster the heating rate.
[0093] Comparative Example 3
[0094] The remaining steps of this comparative example are the same as those of Example 2, except that the titanium carbide in S5 is replaced with 3 g in sequence. The electrothermal and photothermal heating test performance test was carried out under the experimental conditions of 25±2°C and 60±5%RH. The results showed that the maximum temperature rise was basically the same as that of Example 2, indicating that the current epoxy resin content has reached its limit and can no longer load more titanium carbide nanoparticles.
Claims
1. A composite coating for electrothermal and photothermal conversion deicing, characterized in that: The invention comprises the following raw materials in parts by weight: 3.5 to 6 parts of epoxy resin, 3.5 to 6 parts of curing agent, 1 to 2 parts of titanium carbide and 18 to 20 parts of anhydrous ethanol.
2. The composite coating for deicing by electrothermal and photothermal conversion according to claim 1, characterized in that: The curing agent is E51 curing agent, and the epoxy resin is E51 bisphenol A epoxy resin.
3. The composite coating for deicing by electrothermal and photothermal conversion according to claim 1, characterized in that: The average particle size of the titanium carbide is 40 to 80 nm.
4. A method for preparing the composite coating for electrothermal and photothermal conversion deicing according to claim 1, characterized in that: The following steps are involved: Step 1, using anhydrous ethanol as a solvent, adding epoxy resin and curing agent and stirring at room temperature until dissolved to obtain a homogeneous solution A; Step 2, applying the homogeneous solution A obtained in step 2 on the surface of a clean substrate (1) by scraping, and vacuum drying to form an insulating layer (2) on the clean substrate (1); Step 3, laying a conductive copper foil (3) on the insulating layer (2) obtained in step 2; Step 4: using anhydrous ethanol as solvent, adding titanium carbide nanoparticles and magnetically stirring them evenly, then adding epoxy resin and curing agent, magnetically stirring until dissolved, and then ultrasonically dispersing them to form a homogeneous solution B; Step 5, spraying the homogeneous solution B obtained in step 4 on the surface of the product obtained in step 3, and vacuum drying to obtain a composite coating.
5. The method for preparing a composite coating for electrothermal and photothermal conversion deicing according to claim 4, characterized in that: In the step 1, the mass ratio of anhydrous ethanol, epoxy resin and curing agent is 2-3:0.5-2:0.5-2.
6. The method for preparing a composite coating for electrothermal and photothermal conversion deicing according to claim 4, characterized in that: In the step 2, the vacuum drying temperature is 60 to 80° C. and the time is 2 to 4 hours.
7. The method for preparing a composite coating for electrothermal and photothermal conversion deicing according to claim 4, characterized in that: In the step 2, the substrate (1) is an iron plate, the surface of which is first treated with 800-2000 mesh sandpaper to remove surface impurities, and then ultrasonically cleaned for 10-20 minutes to form a clean surface.
8. The method for preparing a composite coating for electrothermal and photothermal conversion deicing according to claim 4, characterized in that: In the step 4, the ratio of anhydrous ethanol, titanium carbide, epoxy resin: curing agent is 7.5-8.5:1-2:0.25-1:0.25-1.
9. The method for preparing a composite coating for electrothermal and photothermal conversion deicing according to claim 4, characterized in that: In the step 4, the rotation speed of the magnetic stirring is 500 to 600 rpm, and the time is 40 to 60 min.
10. The method for preparing a composite coating for electrothermal and photothermal conversion deicing according to claim 4, characterized in that: In the step five, the spraying is air spraying, the compressed air pressure of the spraying is 0.4-0.8 MPa, the distance between the substrate and the spray gun nozzle during the spraying process is 15-20 cm, the spraying time is 30-60 s, the vacuum drying temperature is 60-80° C., and the time is 4-8 hours.
Citation Information
Patent Citations
Anti-icing material with electrothermal photothermal conversion capability and wear-resistant and super-hydrophobic multiple properties as well as preparation method and application of anti-icing material
CN114656857A
Super-hydrophobic cement-based anti-icing / deicing coating with efficient photothermal conversion performance and preparation method of super-hydrophobic cement-based anti-icing / deicing coating
CN118460105A